El diseño editorial como apoyo para la práctica y fortalecimiento de los valores ciudadanos en niños de 3-5 años de Unidad Educativa Nicolás Martínez - Eugenio Caisaguano, Marjorie Anabel (2023)
The investigation project has the purpose of establishing how the editorial design helps the practice and strengthening of citizen values in children from 3-5 years old of the Nicolás Martínez Educational Unit, this arises from the problems of today's society, mostly caused by the inhabitants with a lack of knowledge of citizen values. For this it is necessary that human beings, from their beginnings, have a rich formation in civic values, the main ones in charge are the families in which the children develop day by day. When children turn 3 years old, they go to their initial level of education where teachers are in charge of complementing the message. The development of this research was related to the proposed objectives, mainly to recognize the advantages of editorial design as a support tool for the practice and strengthening of values, for which different bibliographic sources were consulted, such as books, magazines, brochures, articles, which allowed supporting the theories and information of the research. As for the methodology, the inductive method was used, with a mixed approach where the qualitative approach was emphasized by collecting information through interviews with preschool teachers, psychologists, and design experts, the information obtained allowed us to perform a congruent triangulation analysis integrating the main ideas of the interviewees that allowed us to have several points of view for the subsequent development of a proposal of didactic material. In addition to confirming the importance of didactic material in early education for the process of practicing and strengthening citizen values, after this evaluation we proposed the design of a booklet focused on activities and cards in order to reinforce the information.